Chemistry : the molecular nature of matter and change - Silberberg, Martin S. [ (Martin Stuart)] , 1945-; Amateis, Patricia G. (McGraw-Hill Education, 2021)
"Chemistry is so crucial to an understanding of medicine and biology, environmental science, and many areas of engineering and industrial processing that it has become a requirement for an increasing number of academic majors. Furthermore, chemical principles lie at the core of some of the key societal issues we face in the 21st century-dealing with climate change, finding new energy options, and supplying nutrition and curing disease on an ever more populated planet. The ninth edition of Chemistry: The Molecular Nature of Matter and Change maintains its standard-setting position among general chemistry textbooks by evolving further to meet the needs of professor and student. The text still contains the most accurate molecular illustrations, consistent step-by-step worked problems, and an extensive collection of end-of-chapter problems. And changes throughout this edition make the text more readable and succinct, the artwork more teachable and modern, and the design more focused and inviting. The three hallmarks that have made this text a market leader are now demonstrated in its pages more clearly than ever"-- Provided by publisher